Behavioral problems among basic education students A case study of students at Samir Yassin School in Latakia - اسماعيل هبه; هناء برقاوي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The problem of the study was launched by revealing the most prominent dimensions of behavioral problems prevalent among basic education students attending Samir Yassin School in Latakia Governorate as a model, in addition to identifying the most behavioral problems, which were repeatedly identified in this research in four areas (theft, lying, aggression, anger, and stubbornness). Among members of the research community. The questionnaire was distributed to all members of the research community (students at Samir Yassin School for Basic Education in Latakia), who numbered 633 students distributed from the first grade to the sixth grade. The research reached several results, including the most common behavioral problems among members of the research community, which is aggression. The results also revealed the most prominent dimensions of the four behavioral problems that the current research addressed (theft, lying, aggression, anger, and stubbornness), according to the frequencies of the members of the research community.